Answers

2014-08-26T19:53:59+05:30

This Is a Certified Answer

×
Certified answers contain reliable, trustworthy information vouched for by a hand-picked team of experts. Brainly has millions of high quality answers, all of them carefully moderated by our most trusted community members, but certified answers are the finest of the finest.
subsitution:
equation 1: x=1
equation 2: x + y = 2
substitute 1 in 2 
1 + y = 2
y = 2 - 1 (when 1 goes that side it becomes negative)
y = 1
elimination:
eq 1 : x + y -2 = 0
eq 2 : x - y - 4 = 0
if we eliminate y we get:
x -2 = 0
x - 4 = 0
add both,we get
2x -6 = 0
2x = 6
x = 3

1 5 1
  • Brainly User
2014-08-26T20:03:51+05:30
Substitution:-

Step 1: 5x + 3y = 26              [Equation 1.]   
Step 2: x - 3y = 4                 [Equation 2.] 
Step 3: x = 3y + 4                 [Rearrange equation 2.]
Step 4: 5(3y + 4) + 3y = 26  [Substitute the values.]
Step 5: 18y + 20 = 26           [Group the like terms.] 
Step 6: 18y = 6      [Subtracting 20 from the two sides of the equation.] 
Step 7:        [Divide throughout by 18.]
Step 8:      [Substitute the values.]
Step 9: x = 5                            [Simplify.]
Step 10: The solution for the linear system is 
0